The collaboration of James Mutch and Franz Boas, 1883-1922 - Harper, Kenn (Études/Inuit/Studies, 2008)
AbstractJames Mutch, whaler and manager of the Scottish whaling station at Kekerten in Cumberland Sound, assisted Franz Boas in his field study of Inuit culture from 1883 to 1884. Subsequently, the two men carried out an extensive correspondence, lasting over thirty years. At Boas invitation, Mutch made three collections of ethnographic material for the American Museum of Natural History, which allowed Boas to publish two major works on Inuit material and intellectual culture without venturing north again. Mutch’s contribution to our knowledge of Inuit culture has never been described and has therefore gone unrecognised.